The digital technologies of information and communication by the prism of digital language - Bersi, Rodrigo Martins [UNESP]; Miguel, Jose Carlos [UNESP]; Arena, Dagoberto Buim [UNESP] (Univ Federal Tocantins, Campus Tocantinopolis, 2019)
This essay analyzes TDIC - Digital Information and Communication Technologies through the prism of language, as it gives the new technologies the status of digital language. It takes aspects of Vygotsky's Historical Cultural Theory, and principles of the philosophy of language discussed by members of the so-called Bakhtin Circle, to interpret digital technologies as a new human language and their implications for education. It is a theoretical reading about TDICs, seen as a revolution in human technique, because it goes beyond the daily perspective of resources as mere instruments. The aim is to highlight its aspects of development, understood as intellectual technology that is configured in the mediation that establishes between the subjects of social and communicative exchange, on the one hand, and learning, on the other, and causes epistemological changes regarding knowledge about learning human. From this perspective, it is possible to recognize the specificities of digital language in relation to orality and writing as an autonomous and under construction language, which allows articulating concepts such as scripts, multimodality and hypertext, as well as implementing notions such as navigation and that of digital utterances. This enriches theoretical and epistemological discussions about TDIC in the educational context, and acknowledges its implications for learning and human development beyond its utilitarian bias.
Keywords: TDIC; Digital Language; Digital Instruments